OpenCL: A Parallel Programming Standard for Heterogeneous Computing Systems - Stone, John E.; Gohara, David; Shi, Guochun (Computing in science & engineering, 2010)
We provide an overview of the key architectural features of recent microprocessor designs and describe the programming model and abstractions provided by OpenCL, a new parallel programming standard targeting these architectures.